Analisis Perbandingan Keakuratan CAPM Dan APT Dalam Upaya Pengambilan Keputusan Investasi Saham Sektor Perbankan - Arif Abdillah; Aditya Kristamtomo Putra (Universitas Medan Area, 2021)
The Capital Asset Pricing Model and the Arbitrage Pricing Theory are a balance model that uses risk measurement variables to see risk correlations and returns. This research is descriptive quantitative. The purpose of this research is to find out how much the value of stock returns in the banking sector is calculated by the Capital Asset Pricing Model and Arbitrage Pricing Theory, looking for a more accurate model and how big is the difference in accuracy of the significant accuracy of the Capital Asset Pricing Model and Arbitrage Pricing Theory in making investment decisions in the banking sector. The population in this study is a banking company registered at Indonesia Stock Exchange during 2015-2018. The sample in this study amounted to 36 banking companies listed on the Indonesia Stock Exchange during 2015-2018. The sampling method is a non-probability sampling method that is purposive sampling technique. The results of this study indicate that the Capital Asset Pricing Model is better than the Arbitrage Pricing Theory and there is no difference in accuracy between the Capital Asset Pricing Model and the Arbitrage Pricing Theory in an investment decision making effort at banking sector.